The Relationship Between Sleep Pattern and the Incidence of Acne Vulgaris in Students of the Faculty of Medicine, YARSI University, Class of 2021 and Its Review According to Islamic Views - Gadis Dari Adn; Purwaningsih, Endang; Ali Ma’sum, Ali Ma’sum (Junior Medical Journal, 2024)
Introduction: Acne Vulgaris is an inflammatory disorder of pilosebasea, which runs chronically and is a self-limiting disease. Acne Vulgaris triggered by Propinobacterium acne in adolescence under the influence of normally circulating dehydroepiandrosterone. Sleep is essential for normal human physiological and biological function, and partially regulated by the suprachiasmatic nucleus located in the anterior hypothalamus. Previous research suggests that there is a significant link between poor sleep patterns and the incidence of Acne vulgaris. In Islam, a good sleep pattern is very important. Muslims should try to imitate the sleep patterns taught by the Prophet SAW so that in the future it does not cause disease or harm to oneself. This study aims to determine the relationship between sleep patterns and the incidence of Acne vulgaris in students of FK YARSI 2021. Methodology: Quantitative analytical research with a cross-sectional approach in students of FK YARSI 2021 with a minimum sample number of 150. Primary data were taken using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the Acne vulgaris observation sheet. The data will be analyzed univariately and bivariately on SPSS using the Chi-Square test with a p-value of <0.05. Results: Univariate analysis showed that the majority of respondents had poor sleep patterns (99.3%) and had Acne vulgaris (50.7%). Bivariate analysis showed no significant association between sleep patterns and the incidence of Acne vulgaris (p>0.05). Conclusion: There is no significant relationship between sleep patterns and the incidence of Acne vulgaris vulgaris in Students of FK YARSI 2021.